From the book to the library or the arborescent effect in Zabor ou Les Psaumes by Kamel Daoud - Mecheri, Lamia; GOUASMIA, Chourouk Edoha (Journal of Human Sciences, 2022)
In this literary study, conducted from the perspective of the narratology, we are interested in the novel of Kamel Daoud, Zabor ou Les Psaumes (2017). In this contemporary story, we will analyze the network effect of books and their relationship to the power of writing, a gift to the protagonist Zabor.